Recycling the Cycle : The City of Chester and Its Whitsun Plays - Mills, David, 1938- (Book collections on Project MUSE., 1998)
"A consciousness of the past has been an essential determinant of community in the city of Chester, England. In particular, the city's Whitsun Plays have been a vehicle for communicating the myth of the city's medieval heritage, helping to reinforce the sense of history that is part of Chester's identity." "Building upon the material in REED: Chester, David Mills has produced a detailed study of Chester's Whitsun Plays in their local, physical, social, political, cultural, and religious contexts. A continuum has survived between the Middle Ages and the present day, providing not only an understanding of the plays themselves, but a narrative of the ways in which manuscripts survive and the functions that they serve. The continued performance of these plays is significant of modern play revivals as a political and sociological phenomenon, demonstrating the power that these rituals and plays still hold."--Jacket.